Prove The Following - 3 (Quadratic Equations)

This note facilitates you to prove good questions based on Quadratic Equations. So please use this note. I will try my best to post these types of notes from now.


\(\color{green}\text{Prove the Following :}\)

  1. If the sum of the roots of the equation \(px^2 + qx + r = 0\) be equal to the sum of their squares, show that \(2pr = pq + q^2\)

  2. If the difference of roots of \(x^2 - bx + c = 0\) be same as that of the roots of \(x^2 - cx + b = 0\) then prove that \(b + c = -4\) and \(b = c\)

  3. If the roots of the equation \(\dfrac{1}{(x + p)} + \dfrac{1}{(x + q)} = \dfrac{1}{r}\) are equal in magnitude but opposite in sign, show that \(p + q = 2r\) and product of the roots is equal to \(-\dfrac{1}{2}(p^2 + q^2)\)

  4. If the ratio of the roots of the equation \(ax^2 + bx + c = 0\) is \(r\), then prove that \(\dfrac{(r + 1)^2}{r} = \dfrac{b^2}{ac}\)

  5. If the ratio of the roots of the equation \(x^2 + px + q = 0\) be equal to the ratio of roots of the equation \(x^2 + bx + c = 0\), then prove that \(p^2c = b^2q\)

  6. If the sum of the two roots of the equation \(x^3 - px^2 + qx - r = 0\) is zero, then prove that \(pq = r\)

  7. If the equations \(ax^2 + bx + c = 0\) and \(bx^2 + cx + a = 0\) have a common root than prove that \(a^3 + b^3 + c^3 = 3abc\) and \(a = 0\)


If anybody proved any one of these I will mark that question as proved. But if you have another idea to the same question you can post it too. So I will also mention in how many methods the proof is proved. Try your best to prove these.


For more of these see my set Proof Based Notes

Note by Ram Mohith
2 weeks, 3 days ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Eliminate x and y sin(x) + sin(y) = a cos(x) + cos(y) = b tan(x) + tan(y) = c

Rahul Sharma - 6 days, 8 hours ago

Log in to reply

1) Let the roots of the equation \(px^2 + qx + r = 0\) be \(a,b\)

Given : \(a + b = a^2 + b^2\)

\(\implies a + b = (a + b)^2 - 2ab\)

\(\implies -\dfrac{q}{p} = \dfrac{q^2}{p^2} - \dfrac{2r}{p}\)

\(\implies - pq = q^2 - 2pr\) (Multiplying all terms by \(p^2\))

\(\implies 2pr = pq + q^2\)

\(\color{green}\text{Hence Proved}\)

Ram Mohith - 1 week, 4 days ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...